Kultivasi Limbah Organik Menjadi Maggot Black Soldier Fly (BSF) sebagai Pemberdayaan Ekonomi Masyarakat Di Desa Kori Kecamatan Sawoo Kabupaten Ponorogo - Fatmawati, Indah; Jhohari, Nur Alfian; Aprilia, Novita (Jurnal Al Basirah, 2025)
Community empowerment through organic waste management can be one of the solutions in improving the local economy. One of the innovative approaches in organic waste treatment is the cultivation of Black Soldier Fly Maggot (BSF) which has great potential in producing animal feed and other products and has economic value. Seeing the potential that exists in Puhcacing Hamlet, Kori Village, Sawoo District, Ponorogo Regency, as the location for the implementation of the Real Work Lecture (KNN), students and Field Supervisors (DPL) of the Riyadlotul Mujahidin Islamic Institute of KKN conducted Community Service (PKM) in the form of community empowerment through BSF Maggot cultivation as a solution to organic waste management which also aims to increase community income. The method of implementing PKM is carried out by providing training to the community on how to cultivate BSF Maggot using household and agricultural organic waste as a breeding medium. The results of this PKM are expected to improve community welfare through waste reduction, the creation of business opportunities, and the development of derivative products from Maggot BSF that can be used in the livestock and organic fertilizer industries. This program is also expected to introduce sustainable environmentally friendly technology for the local community.